2019
DOI: 10.1128/aac.01743-18
|View full text |Cite
|
Sign up to set email alerts
|

Dalbavancin Alone and in Combination with Ceftaroline against Four Different Phenotypes of Staphylococcus aureus in a Simulated Pharmacodynamic/Pharmacokinetic Model

Abstract: Glycopeptides such as vancomycin have been used as the first-line therapy against MRSA infections for over half a century. Reduced susceptibility and emergence of resistance to first-generation glycopeptides has led to development of second-generation lipoglycopeptide derivatives such as dalbavancin which hold broader ranges of activity and enhanced pharmacokinetic properties. We evaluated the MIC values for a total of 100 isolates, including 25 methicillin-resistant Staphylococcus aureus (MRSA), 25 heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The inverse was also shown, in which antibiotics induced a phenotypic change in bacteria that caused increased predation by phages . Interestingly, a similar hypothesis, known as the seesaw effect, was also shown between β‐lactams and glycopeptides/lipopeptides with S. aureus …”
Section: Rationale For Bacteriophage and Antibiotic Combinationsmentioning
confidence: 74%
“…The inverse was also shown, in which antibiotics induced a phenotypic change in bacteria that caused increased predation by phages . Interestingly, a similar hypothesis, known as the seesaw effect, was also shown between β‐lactams and glycopeptides/lipopeptides with S. aureus …”
Section: Rationale For Bacteriophage and Antibiotic Combinationsmentioning
confidence: 74%
“…We have generated new insights into the mechanisms of dalbavancin resistance, cross-resistance, and the seesaw effect; however, the demonstrated efficacy of dalbavancin in our models should be interpreted cautiously. Another in vitro study with a similar design demonstrated sustained bactericidal activity of dalbavancin against MRSA strains for !7 days, but that study appears to have used concentrations far exceeding reasonable free-drug exposures expected in a patient, and their model was continued for only 7 days [42]. Resistance to dalbavancin in our models only emerged from days 11e18.…”
Section: Discussionmentioning
confidence: 97%
“…(EasySpiral Pro, Intersciences, Worborn, MA, USA). In an effort to eliminate the DAL carryover in the DAL-containing samples (DAL alone and DAL + CFZ), the centrifugation method was utilized twice as reported previously [ 32 ]. Briefly, the samples were centrifuged, following the centrifugation 0.9 mL of the supernatant was removed, and 0.9 ml of normal saline was added in its place.…”
Section: Methodsmentioning
confidence: 99%
“…The DAP PK evaluations were confirmed by a validated high-performance liquid chromatography assay that conformed to the guidelines set forth by the College of American Pathologists [ 38 ]. The VAN samples were analyzed using our HPLC methods, as previously described [ 32 ]. The HPLC assays demonstrated a coefficient of variation less than 10% for all standards, performed in duplicate.…”
Section: Methodsmentioning
confidence: 99%